LPV-based Control Design of an Adaptive Cruise Control System for Road Vehicles. Issue 14 (2015) - Németh, Balázs; Gáspár, Péter; Orjuela, Rodolfo; Basset, Michel
Abstract: The paper presents a robust cruise control design method for a test vehicle, which is able to guarantee velocity tracking performance. The longitudinal dynamics and the consideration of model uncertainties such as parameters variation and actuator dynamics, are formulated in the vehicle model. The proposed controller has a feedforward term, which reduces the conservativeness of the control system during the compensation of the measured disturbances. The feedback term is designed using robust Linear Parameter-Varying methods, in which the inaccuracy of the feedforward control is considered. The purpose of the feedback control is to guarantee the robust performance and to handle the actuator saturation. The efciency of the method is presented through simulation scenarios.